PENGARUH BRAND CREDIBILITY TERHADAP INFORMATION EFFICIENCY DAN RISK REDUCTION, SERTA DAMPAKNYA ATAS REPURCHASE INTENTION - Aekram Faisal (Jurnal Manajemen dan Pemasaran Jasa, 2015)
This research conducted to know the influence of Brand Credibility to Information efficiency andRisk reduction, also the influence of Information efficiency and Risk reduction to Repurchaseintention. This research aimed to know the influence of Brand Credibility to Repurchase intentionthat mediated by Information efficiency and Risk reduction. The methodology of this research istesting hypothesis research. The sample collecting by questionnaire of 150 respondents fromStarbucks Coffee who visit Starbucks Coffee minimum 2 times in the last 2 months. The samplecollection tchenique used in this research is purposive sampling. The analysis tool is structuralequation model (SEM). The result of this research showed there is an influence of brand credibilityto information efficiency, also found the influence of brand credibility to risk reduction, theinfluence information efficiency to repurchase intention, and influence risk reduction to repurchaseintention. This research conducted in the limited field, that is Starbuck Coffee in West Jakarta areaonly and this research do not put others variables such as related variable to Brand credibility. Theimplication of this reseach is manager able to apply marketing strategy to improve repurchaseintention. This research able to be as reference for marketing to apply the strategy to improvetheir selling.Keywords: Brand Credibility, Information efficiency, Risk reduction, Repurchase intention